Efficacy of Environmental Cleaning Protocol Featuring Real-Time Feedback with and without PX-UV in Reducing the Contamination of Gram-Negative Microorganisms on High-Touch Surfaces in Four Intensive Care Units in Thailand - Ornnicha Sathitakorn; Kittiya Jantarathaneewat; David J Weber; Piyaporn Apisarnthanarak; Sasinuch Rutjanawech; Anucha Apisarnthanarak (MDPI AG, 2023)
Environmental cleaning and disinfection practices have been shown to reduce microorganism bioburden in the healthcare environment. This study was performed in four intensive care units in Thailand. Five high-touch surfaces were sampled before and after terminal manual cleaning and disinfection, and after pulsed xenon UV (PX-UV). Five nursing station sites were collected on a weekly basis before and after terminal manual cleaning. There were 100 patient rooms-50 rooms in the intervention arm and 50 rooms in the control arm-plus 32 nursing station sites. In the intervention arm, rooms with positive Gram-negative microorganisms were reduced by 50% after terminal manual cleaning and disinfection (p = 0.04) and 100% after PX-UV disinfection (p < 0.001). On five nursing station sites, colony counts of Gram-negative contamination decreased by 100% (p < 0.001) in the intervention arm while decreasing by 65.2% (p = 0.03) in the control arm after terminal manual cleaning and disinfection. The in-room time use was 15.6 min per room. A PX-UV device significantly reduced the level of Gram-negative microorganisms on high-touch surfaces in intensive care units. The application of a PX-UV device was practical a in resource-limited setting without compromising cleaning and disinfection times.